2019
DOI: 10.3390/pharmaceutics11060286
|View full text |Cite
|
Sign up to set email alerts
|

Novel Population Pharmacokinetic Approach to Explain the Differences between Cystic Fibrosis Patients and Healthy Volunteers via Protein Binding

Abstract: The pharmacokinetics in patients with cystic fibrosis (CF) has long been thought to differ considerably from that in healthy volunteers. For highly protein bound β-lactams, profound pharmacokinetic differences were observed between comparatively morbid patients with CF and healthy volunteers. These differences could be explained by body weight and body composition for β-lactams with low protein binding. This study aimed to develop a novel population modeling approach to describe the pharmacokinetic differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…More recent studies used body size and body composition (with body surface area or lean body mass) to compare CF patients and healthy volunteers. They found that in CF patients who were not underweight V d for ß-lactam antibiotics was similar to that of non-CF patients [47,48]. Thus, in normal nourished CF patients, the dose per kg of bodyweight may be similar to healthy controls, whereas underweight CF patients may require a larger dose per kg of bodyweight.…”
Section: (Volume Of) Distributionmentioning
confidence: 90%
See 3 more Smart Citations
“…More recent studies used body size and body composition (with body surface area or lean body mass) to compare CF patients and healthy volunteers. They found that in CF patients who were not underweight V d for ß-lactam antibiotics was similar to that of non-CF patients [47,48]. Thus, in normal nourished CF patients, the dose per kg of bodyweight may be similar to healthy controls, whereas underweight CF patients may require a larger dose per kg of bodyweight.…”
Section: (Volume Of) Distributionmentioning
confidence: 90%
“…Antibiotics bind reversibly to plasma proteins (serum albumin, alpha-1 acid glycoprotein, and lipoproteins). Decreased plasma protein binding for some antibiotics, especially multiple ß-lactam antibiotics [47], is observed in people with CF (mostly adults combined with a few adolescents), of which the precise mechanism is not completely understood [47,48]. Increased inflammatory processes that occur during acute pulmonary exacerbations may result in decreased production of albumin and, in addition, may alter albumin and protein binding of drugs [49].…”
Section: (Volume Of) Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Otherwise, the population analysis problem is the same. Bulitta et al [ 38 ] and Shah et al [ 39 ] use the method S-ADAPT. S-ADAPT is based on the ADAPT package developed by D’Argenio, Wang and Schumitzky.…”
Section: Supplementary Materialsmentioning
confidence: 99%